Enhancing Communication Skill in Lobby, Presentation, and Negotitation via Project-Based Digital Simulation - Andi Atrianingsih; Zulkifli Tahir; Muhammad Yahya; Diana Rina (Universitas Pendidikan Ganesha, 2026)
This study explores the application of Project-Based Learning (PjBL) based on digital simulation in the learning of the Lobbying, Presentation, and Negotiation Engineering Course, as well as its contribution to students' interpersonal communication competencies and life skills. Using a descriptive qualitative approach with reflexive thematic analysis, data were obtained from 10 group simulation video documents, in-depth interviews, and classroom practical observations. The results showed that the integration of PjBL and digital simulation encouraged improved verbal and nonverbal communication, critical thinking, empathy, and self-management, as well as more confident and strategic communication expressions. The collaborative process strengthens self-expression and critical reflection, which is the foundation of life skills development. The findings confirm that project-based digital simulations are effective as a communication learning strategy, while facilitating the transformation of students' social-cognitive competencies in the digital era.